Circulating microRNAs as biomarkers in patients with allergic rhinitis and asthma - Panganiban, Ronaldo P.; Wang, Yanli; Howrylak, Judie; Chinchilli, Vernon M.; Craig, Timothy J.; August, Avery; Ishmael, Faoud T. (Journal of allergy and clinical immunology, 2016)
MicroRNAs (miRNAs) are emerging as important regulatory molecules that might be involved in the pathogenesis of various diseases. Circulating miRNAs might be noninvasive biomarkers to diagnose and characterize asthma and allergic rhinitis (AR). We sought to determine whether miRNAs are differentially expressed in the blood of asthmatic patients compared with those in the blood of nonasthmatic patients with AR and nonallergic nonasthmatic subjects. Furthermore, we sought to establish whether miRNAs could be used to characterize or subtype asthmatic patients. Expression of plasma miRNAs was measured by using real-time quantitative PCR in 35 asthmatic patients, 25 nonasthmatic patients with AR, and 19 nonallergic nonasthmatic subjects. Differentially expressed miRNAs were identified by using Kruskal-Wallis 1-way ANOVA with Bonferroni P value adjustment to correct for multiple comparisons. A random forest classification algorithm combined with a leave-one-out cross-validation approach was implemented to assess the predictive capacities of the profiled miRNAs. We identified 30 miRNAs that were differentially expressed among healthy, allergic, and asthmatic subjects. These miRNAs fit into 5 different expression pattern groups. Among asthmatic patients, miRNA expression profiles identified 2 subtypes that differed by high or low peripheral eosinophil levels. Circulating miR-125b, miR-16, miR-299-5p, miR-126, miR-206, and miR-133b levels were most predictive of allergic and asthmatic status. Subsets of circulating miRNAs are uniquely expressed in patients with AR and asthmatic patients and have potential for use as noninvasive biomarkers to diagnose and characterize these diseases.